2011
DOI: 10.3382/ps.2010-01005
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and modeling true metabolizable energy of sorghum grain for poultry

Abstract: Sorghum grain is an important ingredient in poultry diets. The TMEn content of sorghum grain is a measure of its quality. As for the other feed ingredients, the biological procedure used to determine the TMEn value of sorghum grain is costly and time consuming. Therefore, it is necessary to find an alternative method to accurately estimate the TMEn content. In this study, 2 methods of regression and artificial neural network (ANN) were developed to describe the TMEn value of sorghum grain based on chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…Amino acid digestibilities, AME and TME of the tannin varieties were low in the present study. Condensed tannins have been reported to reduce feed intake (Oduhu & Baker, 2005;Bryden et al, 2009), metabolizable energy (Bryden et al, 2009;Perez-Maldonado & Rodrigues, 2009;Sannamani et al, 2010;Sedghi et al, 2011) and amino acid digestibility (Selle et al, 2010;Ebadi et al, 2011) in broilers. Such limiting factors are the result of the poor nutritional quality of the protein (kafirins and glutelin) and subsequently attributed to low solubility and deficiencies in amino acids (Sastry et al, 1986;Selle et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid digestibilities, AME and TME of the tannin varieties were low in the present study. Condensed tannins have been reported to reduce feed intake (Oduhu & Baker, 2005;Bryden et al, 2009), metabolizable energy (Bryden et al, 2009;Perez-Maldonado & Rodrigues, 2009;Sannamani et al, 2010;Sedghi et al, 2011) and amino acid digestibility (Selle et al, 2010;Ebadi et al, 2011) in broilers. Such limiting factors are the result of the poor nutritional quality of the protein (kafirins and glutelin) and subsequently attributed to low solubility and deficiencies in amino acids (Sastry et al, 1986;Selle et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The adaptive agronomic characteristics of sorghum make it suitable for cultivation in different environmental conditions. Sorghum varieties have been used for many years for poultry and human consumption, especially in Africa and Asia, and have been shown to vary in physical and chemical characteristics (Neucere & Sumrell, 1980;Sedghi et al, 2011). While some authors have reported anti-nutritional factors in sorghum grain that have adverse effects on the utilization of sorghum protein and metabolizable energy by poultry, such as tannins (Gous et al, 1982;Boren & Waniska, 1992), others have stated that these factors do not always reduce the performance of poultry (Nyachoti et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Model performance was assessed after generating output by the models. Previous studies have shown the ability of ANN to estimate the TME n of poultry feedstuffs based on their chemical composition (Ahmadi et al, 2008;Sedghi et al, 2011). The results of our study reveal that the SVR approach offers a competitive alternative to existing powerful ANN models.…”
Section: Calibrationmentioning
confidence: 57%
“…Recently, artif icial neural network (ANN) models have received attention among poultry nutritionists, e.g. for estimating the ME of poultry offal meal (Ahmadi et al, 2008) and sorghum grain (Sedghi et al, 2011) …”
mentioning
confidence: 99%
“…Flavonoids in sorghums include phenolic compounds, of which, tannins and anthocyanins are the most important flavonoids isolated from sorghum (Rooney and Waniska, 2000;. Tannin content in the pericarp is one of the most important factors affecting the feed value of sorghum grain, since it adversely affects the metabolizable energy in grain and protein utilization by poultry (Sedghi et al, 2011). The most common anthocyanins in sorghum are the 3-deoxyanthocyanidins, which include luteolinidin and apigeninidin ).…”
Section: Introductionmentioning
confidence: 99%